2021
DOI: 10.7150/jca.57678
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Biomarkers in Squamous Cell Carcinoma of the Anal Canal (SCCAC) and their Influence on Treatment Outcomes

Abstract: Background: Although Chemoradiation (CRT) is the curative treatment for SCCAC, many patients present primary resistance. Since it is a rare tumor, response predictors remain unknown. Methods: We performed a prospective cohort study to evaluate biomarkers associated with CRT response, progression-free survival (PFS), and overall survival (OS). The primary endpoint was response at 6 months (m). Tumor DNA and HPV were analyzed by next-generation sequencing, while KI-67 and PD-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Clinical practice guidelines indicate that patients could achieve a response rate of 80%, and the remaining 15% can receive abdominal perineal resection as a salvage treatment. In terms of achieving a CR, our CR rate at 6 months was 70%, which is lower than the 90.5% rate observed in the ACT II trial at 26 weeks, but is similar to prospective trials or multicentric series with similar baseline clinical staging, where the CR rates reported were between 65% and 70% for locally advanced disease [ 37 ]. We showed in our study that CR is a good surrogate of long-term outcomes as it was associated with better PFS and OS.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Clinical practice guidelines indicate that patients could achieve a response rate of 80%, and the remaining 15% can receive abdominal perineal resection as a salvage treatment. In terms of achieving a CR, our CR rate at 6 months was 70%, which is lower than the 90.5% rate observed in the ACT II trial at 26 weeks, but is similar to prospective trials or multicentric series with similar baseline clinical staging, where the CR rates reported were between 65% and 70% for locally advanced disease [ 37 ]. We showed in our study that CR is a good surrogate of long-term outcomes as it was associated with better PFS and OS.…”
Section: Discussionsupporting
confidence: 61%
“…This could be related to the reduced number of ASCC without HPV infection detected in our overall cohort. Moreover, efforts to stratify patients according to the HPV status were made, but its place in clinical practice remains controversial given heterogeneous results for its prognostic role [ 36 , 37 ]. One likely possibility is that retrospective cohorts evaluated in the available meta-analysis had selection biases and confounders that influenced the results [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic review and meta-analysis of 17 retrospective cohort studies demonstrated that HPV+ and p16+ tumors had improved OS compared to tumors with negative profiles [ 41 ]. On the other hand, a prospective cohort with multivariable analyses of non-metastatic patients treated with standard CRT did not show a difference in 5-year OS according to HPV status [ 42 ]. Currently, there are no recommendations for treatment modification based on HPV or p16 status ( Table 1 ).…”
Section: Biomarkersmentioning
confidence: 99%
“…Data regarding clinical outcomes of HIV+ SCCA patients are scarce. Studies on the prognostic and predictive impact of HIV status report conflicting results [ 42 ].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation